STRATEGY OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN LEARNING FIQIH THAHARAH - Darma Syahputra, Nursalimah, Endi Zunaedy Pasaribu (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
In this study, the researcher used qualitative descriptive research. In addition, data analysis methods such as data reduction, data presentation, and drawing conclusions. The location of the study was at SMP Negeri 2 Satap Pangkatan and the research period was one month. Teachers and students were used as research subjects. Documentation, photos, interview guidelines, and observation sheets were research tools. The research findings showed that: (1) The Islamic Religious Education Fiqh Curriculum of SMP Negeri 2 Satap Pangkatan uses a cooperative approach where teachers help students feel interdependent on each other. This method is a learning approach that uses small groups, especially four to six people from various backgrounds, or a grouping system. (2) Challenges in learning Islamic Fiqh at Madrasah SMP Negeri 2 Satap Pangkatan and its solutions include the inability of students to focus on class activities, causing students to not understand the information being taught. This hinders both learning objectives and the learning process. The solution sought by teachers is to explain again to students who do not understand and who do not listen to what the teacher explains